Discovery of receptor‐ligand interfaces in the immunoglobulin superfamily. Issue 1 (29th July 2019) - Gil, Nelson; Fajardo, Eduardo J.; Fiser, Andras
Abstract: Cell‐surface‐anchored immunoglobulin superfamily (IgSF) proteins are widespread throughout the human proteome, forming crucial components of diverse biological processes including immunity, cell‐cell adhesion, and carcinogenesis. IgSF proteins generally function through protein‐protein interactions carried out between extracellular, membrane‐bound proteins on adjacent cells, known as trans ‐binding interfaces. These protein‐protein interactions constitute a class of pharmaceutical targets important in the treatment of autoimmune diseases, chronic infections, and cancer. A molecular‐level understanding of IgSF protein‐protein interactions would greatly benefit further drug development. A critical step toward this goal is the reliable identification of IgSF trans ‐binding interfaces. We propose a novel combination of structure and sequence information to identify trans ‐binding interfaces in IgSF proteins. We developed a structure‐based binding interface prediction approach that can identify broad regions of the protein surface that encompass the binding interfaces and suggests that IgSF proteins possess binding supersites. These interfaces could theoretically be pinpointed using sequence‐based conservation analysis, with performance approaching the theoretical upper limit of binding interface prediction accuracy, but achieving this in practice is limited by the current ability to identify an appropriate multiple sequence alignment for conservation analysis. However, an important contribution of combining the two orthogonal methods is that agreement between these approaches can estimate the reliability of the predictions. This approach was benchmarked on the set of 22 IgSF proteins with experimentally solved structures in complex with their ligands. Additionally, we provide structure‐based predictions and reliability scores for the 62 IgSF proteins with known structure but yet uncharacterized binding interfaces.